Effect Of AC Compressor Modification on Fuel Consumption in Car - Mokh Hairul Bahri; Dudi Irawan; Adi Pratama Putra (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
The cooling system is a refrigeration technology that is growing, especially regarding the cooling medium (refrigerant), new vehicles nowadays mostly use air conditioning to condition the air in the vehicle's cabin, but for now, there are still many aspects that have not been given much attention, especially the compressor. Compressor systems in vehicles still rely on the engine as a direct drive resulting in increasingly wasteful fuel consumption and reducing the performance of the vehicle. This study analyzes the results of modifying a conventional compressor into an electric compressor by utilizing a split AC compressor whose supply voltage is obtained from a DC to AC inverter on vehicle fuel consumption and the required electrical energy. Inverter modification is highly recommended in the application of car air conditioners, split AC compressors, and others. The results of this research show that AC compressors using split compressors affect fuel consumption.